Gender differences in willingness to compete: The role of public observability - Thomas Buser; Eva Ranehill; Roel van Veldhuizen (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2017)
A recent literature emphasizes the importance of the gender gap in willingness to compete as a partial explanation for gender differences in labor market outcomes. However, whereas experiments investigating willingness to compete typically do so in anonymous environments, real world competitions often have a more public nature, which introduces potential social image concerns. If such image concerns are important, we should expect public observability to further exacerbate the gender gap. We test this prediction using a laboratory experiment that varies whether the decision to compete, and its outcome, is publicly observable. Across four different treatments, however, all treatment effects are close to zero. We conclude that the public observability of decisions and outcomes does not exert a significant impact on male or female willingness to compete, indicating that the role of social image concerns related to competitive decisions may be limited.
Keywords: C91; D03; J16; 330; gender differences; competitiveness; social image; experiment